Fracture toughness testing of a weldable steel - Al-Hadithy, Nabil Abdul-Jalil (Cranfield University, 1981)
The mechanical anisotropies of two varieties of BS 4360 50D steel were demonstrated for tensile, Charpy V impact and COD testing. The detrimental effect of sulphide inclusions for through thickness behaviour was related to the total inclusion length per unit area and the interaction of inclusions within the plastic zone. Sulphide inclusions in the through thickness orientation were found to increase crack tip constraints, reduce the plastic zone size and the post-yield load bearing capacity of the specimen ligament. This was achieved by the ease of movement of the growing crack tip to various planes containing suitable clusters of inclusions. COD at maximum load was shown to decrease exponentially with increasing inclusion content. For acceptable through thickness toughness it was shown necessary to limit the inclusion density to 1 to 1.5mm/mm2, according to the constraints in its application. For plate or pipe material made from highly rolled steel, low sulphur steel melts must be used. Even rare-earth-modified steels will show unacceptable inclusion densities after high rolling strains in the mill. The inclusion density would increase both in the ZR and ZT through thickness directions. Notches along the rolling plane gave lower toughness levels due to inclusion interactions out-of-plane facilitated by the added length of the inclusion caused by hot rolling. A computer program was included which uses a polynomial fitting technique relating COD to inclusion density to predict through thickness toughness for any given inclusion content. A method was devised for through thickness testing of thin plate materials. Valid maximum load COD values were obtained by friction welding of extensions to undersized specimens. The effect of free surfaces that interacted with the plastic zone at the crack tip were found to be beneficial to crack tip deformations. For these reasons thin plates were shown to be unsusceptible to through thickness failures, such as, lamellar tearing, unless the effects of the free surface were removed by welding attachments to the surface. At upper shelf temperatures for ductile structural materials, it was shown that the measured toughness was related to the size of the plastic zone and, hence, to specimen geometry. The measured toughness related more to the absolute length of uncracked ligament rather than to crack length or crack length to width ratio. To -achieve geometry independence, the ligament length was required to be greater than the characteristic plastic zone size for the specimen thickness and testing temperature. The extensive plastic zone and the small highly strained zone sizes were shown to be dependent on temperature. At high temperatures the crack tip strains increased which resulted in crack blunting and stress dissipation. The work hardened material ahead of the crack tip showed evidence of small crack fissuring which led to stable crack growth. At low temperatures, where brittle fracture occurred, the highly strained region and extensive plastic zone were much smaller in size. Crack blunting was greatly reduced which allowed brittle fracture stresses to be achieved at the crack tip. At intermediate temperatures the crack tip blunting was extensive and it was shown that the amount of ductile cracking required to increase the constraint necessary to achieve brittle fracture decreased with decreasing temperature. Large specimen sizes resulted in high stored energy which, at transition temperatures, drove the ductile crack to catastrophic failures. This resulted in narrower transition regions which effectively shifted the transition to higher temperatures. The transition from ductile to brittle behaviour was considered, from the experimental evidence supplied, not to represent a shift in the state of stress. The through-thickness strain decrease associated with this transition was a result'of the associated decrease in COD. As the COD was shown to vary with specimen geometry independently of specimen thickness and, hence, independ- ently of the state of stress, then the associated change in through thickness strains were also not indicative of a change in the state of stress. A shift in the state of stress was considered to occur only when the through thickness strains varied with respect to COD. The method of load application was shown to have a significant effect on the measured toughness. Generally yielded specimens were shown to be under greater crack tip constraints when the specimen was loaded in bending rather then in tension.